Blinded by Beauty? Physical Attractiveness and Candidate Selection in the U.S. House of Representatives1. (22nd April 2015) - Stockemer, Daniel; Praino, Rodrigo
<x xml:space="preserve">Abstract</x> Objective In this article we show that physical attractiveness matters as a heuristic device for uninformed voters but not for politically savvy voters. Methods Drawing on a two‐step experiment, we first ask over 100 students to rank the physical attractiveness of candidates to the U.S. House of Representatives. Second, we create a treatment and a control group comprising each of 1, 200 research different subjects. We ask the first group to indicate their vote choice by merely looking at the picture of candidates for the 2008 U.S. House of Representatives elections, while the second group has a picture and a detailed description of the political/professional competence of the contenders at their disposal. Results We find that our first group of study subjects representing all those voters who are politically uninformed tend to cast their ballot for the better‐looking candidate, whereas the second group, representing politically knowledgeable individuals, choose the more competent candidate. Conclusion Our experimental study provides evidence that uninformed or politically unknowledgeable voters use political appearance as a heuristic device in casing their ballot at elections.